Priorities of Sustainable Building Concept and Evaluation of Possibilities for Energy Efficiency Management of Buildings (As in the Case of Ukraine) - Bohoslovska, Alina; Komelina, Anna; Shcherbinina, Svitlana (International Journal of Engineering and Technology, 2018)
Ensuring the energy efficiency functioning of housing and communal services and increasing the energy efficiency of Ukraine's housing stock, which is one of the largest consumers of heat energy, requires the search for potential opportunities for managing energy efficiency of buildings. Integration into the world economy obliges Ukraine to adhere to international economic principles, one of which is the growth of energy efficiency.The article examines the experience of the world countries in the field of energy efficiency of buildings on the basis of sustainable building concept.Â  The methodology of calculating the integral rating point of the regions of the country based on their energy saving potential is developed. It can be used to evaluate the potential of energy efficiency management of buildings in Ukraine. As a result of the calculations of the integrated estimation of the energy saving potential, an appropriate ranking and grouping of the regions of Ukraine has been carried out.Improvement of the organizational and technical potential of providing energy-efficient functioning of the housing and communal services of Ukraine and the introduction of effective mechanisms for its modernization on the basis of the sustainable building concept should ensure an increase in the efficiency of energy efficiency management of buildings.Â
Keywords: Energy efficiency of buildings. Energy saving potential. Housing. Integrated estimation. Sustainable building.